Ethnic intermarriage in Croatia with special emphasis on the Czech minority - Mrdjen, Snjezana; Bahnik, Maja (Geographica Pannonica, 2018)
This article analyzes interethnic marriage in Croatia in terms of nationality throughout a forty-five year period (1970-2015) on the basis of vital statistics with special consideration of the Czech minority. The usual method of endogamy/exogamy percentage and the odds ratio method were applied. The results show that the percentage of endogamous marriages in Croatia has significantly risen after 1991. Different ethnic groups display various attitudes towards endogamy, ranging from 15 to over 90 percent. Along with Italians, Hungarians and Slovaks, Czechs are less endogamous than other national minorities. Gender differences, contrary to the conclusions in the literature, show that Czech men enter into marriage outside their group less often than Czech women. The change of political climate in Croatia during the 1990s resulted not only in the increase of endogamy, but also affected the structure of mixed marriages among Czechs.